2018
DOI: 10.1016/j.antiviral.2018.03.012
|View full text |Cite
|
Sign up to set email alerts
|

BET bromodomain inhibitors show anti-papillomavirus activity in vitro and block CRPV wart growth in vivo

Abstract: The DNA papillomaviruses infect squamous epithelium and can cause persistent, benign and sometimes malignant hyperproliferative lesions. Effective antiviral drugs to treat human papillomavirus (HPV) infection are lacking and here we investigate the anti-papillomavirus activity of novel epigenetic targeting drugs, BET bromodomain inhibitors. Bromodomain and Extra-Terminal domain (BET) proteins are host proteins which regulate gene transcription, they bind acetylated lysine residues in histones and non-histone p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…Recently, it was reported that the BRD4 inhibitor JQ1 induces depletion of E6 in HPVinduced cervical cancer cells, increasing the sensitivity to cisplatin even in cisplatin-resistant cell lines. More importantly, this effect was observed to be specific to HPV-positive cells, while cisplatin-induced death in HPV-negative cells did not increase [380], as observed in a previous study that used I-BET762 [381]. Similarly, BRD4 inhibition can suppress the tumorigenic effect of HTLV1 Tax protein by inhibiting Nf-kB signaling.…”
Section: Targeting Histone Acetylation (Inhibitors For Hats and Bets)supporting
confidence: 73%
“…Recently, it was reported that the BRD4 inhibitor JQ1 induces depletion of E6 in HPVinduced cervical cancer cells, increasing the sensitivity to cisplatin even in cisplatin-resistant cell lines. More importantly, this effect was observed to be specific to HPV-positive cells, while cisplatin-induced death in HPV-negative cells did not increase [380], as observed in a previous study that used I-BET762 [381]. Similarly, BRD4 inhibition can suppress the tumorigenic effect of HTLV1 Tax protein by inhibiting Nf-kB signaling.…”
Section: Targeting Histone Acetylation (Inhibitors For Hats and Bets)supporting
confidence: 73%
“… Virus Genome Conclusion Reference Porcine reproductive and respiratory syndrome virus (PRRSV) ssRNA EGCG effectively inhibits PRRSV infection and replication in porcine alveolar macrophages. It prevents MARC-145 cells from getting infected from PRRSV Ge et al. (2018) Hepatitis C virus (HCV) ssRNA EGCG prevents infection by inhibiting the entry of HCV into hepatoma cell lines and primary human hepatocytes thus Ciesek et al.…”
Section: Antiviral Properties Of Egcgmentioning
confidence: 99%
“…EGCG was found to inhibit Porcine reproductive and respiratory syndrome virus (PRRSV) infection irrespective of whether it was administered before or after infection; a concentration of 125 μM was enough to completely inhibit the infectivity of viral cells ( Ge et al., 2018 ). In Hepatitis C virus (HCV) infection, EGCG was found out to inhibit the infection by attaching to the target cell and preventing the spread of the infection to different cells ( Calland et al., 2012 ).…”
Section: Antiviral Properties Of Egcgmentioning
confidence: 99%
“…Since the discovery of the first two BET inhibitors GSK525762 and JQ1 ( Filippakopoulos et al, 2010 ; Nicodeme et al, 2010 ), a variety of new BET inhibitors have been developed. They serve a multitude of functions in various tumors, diabetes, chronic kidney failure, coronary artery disease, and other infectious diseases ( Gilan et al, 2020 ; Morse et al, 2018 ; Cochran et al, 2019 ). Their binding site is the BRD-acetyl binding pocket, hence blocking the binding of BET protein to the enhancers and promoters, mainly super-enhancers.…”
Section: Introductionmentioning
confidence: 99%